Fucoidan-based hydrogels particles as versatile carriers for diabetes treatment strategies - Reys, Lara L. (2022)
There is a current lack of fully efficient therapies for diabetes mel-litus, a chronic disease where the metabolism of blood glucose isseverely hindered by a deficit in insulin or cell resistance to thishormone. Therefore, it is crucial to develop new therapeutic strat-egies to treat this disease, including devices for the controlleddelivery of insulin or encapsulation of insulin-producing cells. Inthis work, fucoidan (Fu)â a marine sulfated polysaccharide exhib-iting relevant properties on reducing blood glucose and antioxi-dant and anti-inflammatory effectsâ was used for thedevelopment of versatile carriers envisaging diabetes advancedtherapies. Fu was functionalized by methacrylation (MFu) using8% and 12% (v/v) of methacrylic anhydride and further photo-crosslinked using visible light in the presence of triethanolamineand eosin-y to produce hydrogel particles. Degree of methacryla-tion varied between 2.78 and 6.50, as determined by1HNMR, andthe produced particles have an average diameter ranging from0.63 to 1.3mm (dry state). Insulin (5%) was added to MFu solutionto produce drug-loaded particles and the release profile wasassessed in phosphate buffer solution (PBS) and simulated intes-tinal fluid (SIF) for 24h. Insulin was released in a sustained man-ner during the initial 8 h, reaching then a plateau, higher in PBSthan in SIF, indicating that lower pH favors drug liberation.Moreover, the ability of MFu particles to serve as templates forthe culture of human pancreatic cells was assessed using 1.1B4cell line during up to 7 days. During the culture period studied,pancreatic beta cells were proliferating, with a global viabilityover 80% and tend to form pseudo-islets, thus suggesting thatthe proposed biomaterial could be a good candidate as versatilecarrier for diabetes treatment as they sustain the release of insulinand support pancreatic beta cells viability.